2000
DOI: 10.1177/00220345000790090601
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Antimicrobial Peptide, Human β-defensin 1, in Duct Cells of Minor Salivary Glands and Detection in Saliva

Abstract: The oral cavity is exposed to a variety of environmental insults. Salivary secretions play a critical role in maintaining oral health via innate host defense mechanisms and secretion of secretory IgA. Human beta-defensins (hBD) are antimicrobial peptides that are a component of the innate immune response; they are expressed in epithelia and are proposed to have a role in mucosal defense. hBD-1 mRNA is constitutively expressed in numerous mucosal tissues, including human gingiva and submandibular and parotid gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 35 publications
4
88
1
Order By: Relevance
“…[7][8][9][10] Constitutive expression of antimicrobial peptides has previously been detected in various exocrine glands such as the human cathelicidin LL-37 in sweat glands, the cathelicidin CRAMP in murine salivary glands and ␤-defensins in human salivary glands. [21][22][23] Expression of human ␤-defensin-2 (hBD-2) mRNA in mammary glands was reported by Bals et al 24 in 1998 and recently other groups have found constitutive hBD-1 expression in mammary glandular tissue of nonlactating women as well as in breast tissue during lactation and in breast milk. 25,26 Our finding that hCAP18/LL-37 is expressed in breast cancer cells is novel.…”
Section: Discussionmentioning
confidence: 92%
“…[7][8][9][10] Constitutive expression of antimicrobial peptides has previously been detected in various exocrine glands such as the human cathelicidin LL-37 in sweat glands, the cathelicidin CRAMP in murine salivary glands and ␤-defensins in human salivary glands. [21][22][23] Expression of human ␤-defensin-2 (hBD-2) mRNA in mammary glands was reported by Bals et al 24 in 1998 and recently other groups have found constitutive hBD-1 expression in mammary glandular tissue of nonlactating women as well as in breast tissue during lactation and in breast milk. 25,26 Our finding that hCAP18/LL-37 is expressed in breast cancer cells is novel.…”
Section: Discussionmentioning
confidence: 92%
“…hBD-2 was not detected in human parotid glands [24,34]. In contrast, hBD-1 mRNA is expressed in all human salivary glands and its peptides in duct cells of minor salivary glands as well as in saliva [34,35]. Since hBD-2 is more potent than hBD-1, overexpressing hBD-2 in human saliva appears to be a logical approach for oral infection control.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria and cytokines IL-1 and TNFα upregulate HBD-2 expression in lung and skin epithelial cells [10,28] and induction of HBDs by these stimuli is differentially regulated involving multiple mechanisms [29]. Expression of HBDs in oral tissues has also been extensively studied [23,[30][31][32][33][34][35][36][37][38][39][40]. In gingival epithelium, variable expression levels of HBD-1, -2 or -3 are found in either healthy or diseased gingival tissues [41,42] Previously, we transduced a number of non-HBD-2-expressing cell lines to produce HBD-2 with the notion that these cells may become part of the innate defense mechanisms against infection [6,49].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%